Headmasters Leadership On Task Load And Job Satisfaction Of Special Education Teachers In Malaysia* (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Every country in the world makes education an important element in the development of the country. Through education, human beings are able to know themselves, be aware of their potential and in turn be able to dominate various things. Education is also very important for every human being regardless of race, ethnicity, religion and background to get quality education. Each of us has the right to a proper education, including people with disabilities (PWDs) because they are just like other human beings who need balance in access to information and access to education. Therefore, special education introduced in Malaysia is based on that foundation. However, the delivery of education to these groups is slightly disrupted because the teachers involved are not able to give their full commitment to special education. This situation occurs due to the high workload that needs to be implemented. This workload stems from the incompetent attitude of school leaders. This imbalance has created dissatisfaction in work. This concept article is prepared to explain conceptually the reality that occurs between school leadership, workload and job satisfaction of special education teachers.